Empowering Pig Farmers through the Utilization of Manure into Biogas and Bioslurry - Kalangi, Lidya S.; Mangindaan, Glanny M. Ch.; Elly, Femi H.; Mukhlis (Unram Journal of Community Service, 2025)
Pig manure often creates environmental pollution and social issues for small-scale farmers. This community service activity empowers pig farmers to utilize manure for biogas production as an alternative energy source and as a bioslurry for organic fertilization. We applied socialization and assistance, and constructed dome-type biogas digesters using locally available materials. We analyzed the potential of biogas based on the number of livestock and daily manure production, then connected this to household cooking energy needs. The results indicate that farmers can use the resulting biogas as a substitute for LPG for cooking, reducing their dependence on LPG. Additionally, bioslurry can serve as organic fertilizer, supporting agriculture and household gardens. Socio-economically, this activity enables energy cost savings, improves environmental conditions around pens, and fosters greater social acceptance of pig farming. Overall, transforming livestock manure into biogas and bioslurry provides a sustainable empowerment model for farmers, which communities can replicate.